Giving Dragon Fruit, Apple, and Papaya Juice on Blood Glucose Levels to Diabetes Mellitus Type 2 - Eliza Eliza; Imelda Telisa; Sumarman Sumarman (Jurnal Ilmiah Kesehatan (JIKA), 2022)
Diabetes Mellitus (DM) was a chronic metabolic disorder that occurs when the pancreas fails to produce enough insulin or when the body fails to effectively use the insulin that is produces. One of the non-medical therapies that can be given to patients with diabetes mellitus is giving dragon fruit, apples and papayas. This purpose of this study to see how giving dragon fruit, apple and papaya juice affects blood glucose levels in type 2 diabetes patients. This study is a quasi-experimental design with a pretest and posttest with a control group. This study was carried out at the Palembang Social Health Center from March to October 2022.The sample in this study was selected by accidental sampling with a total sample of 30 subjekts in the treatment and control groups. The paired sample t-test was used to analyze the data, and there was a difference in the average difference of blood glucose levels in the treatment group of 68,44 mg/dl (p-value = 0,000) and the control group of 1,2 mg/dl (p-value = 0,770). Analysis of the multiple linear regression multivariate test showed that there is an effect of energy, fat, carbohydrate and fiber intake on blood glucose levels with a p value <0,005.  The conclution that there is an effect of giving dragon fruit, apple and papaya juice on blood glucose levels in diabetes mellitus type 2 patients the differences in average blood glucose levels of the treatment group were greater than those of the control group.